The influence of social intelligence of secondary school teachers on classroom discipline strategies - Jeloudar, Soleiman Yahyazadeh; Md. Yunus, Aida Suraya; Roslan, Samsilah; Md Nor, Sharifah (Kamla-Raj Enterprises, 2012)
The purpose of this study is to analyze the level of social intelligence among teachers employed in government secondary schools based on a selected demographic variable. The sample of the study comprised 203 teachers. The findings of the study showed that there was a significant difference among the teachers from (Malaysia, India and China) and their social intelligence. The study also revealed that there were significant differences between teachers with high and moderate level of social intelligence in five strategies of classroom discipline used, that is, teachers with high level of social intelligence scored higher in the classroom discipline strategies of discussion, recognition, involvement, and hinting, whereas teachers with moderate level of social intelligence scored higher in the use of aggression. However, no significant difference was found concerning one strategy of classroom discipline (punishment).